Bacterial Adhesion of Streptococcus mutans to Dental Material Surfaces - Kozmos, Mirjam; Virant, Petra; Rojko, Franc; Abram, Anže; Rudolf, Rebeka; Raspor, Peter; Zore, Anamarija; Bohinc, Klemen (Molecules (Basel, Switzerland), 2021)
The aim of this study was to investigate and understand bacterial adhesion to different dental material surfaces like amalgam, Chromasit, an Co-Cr alloy, an IPS InLine ceramic, yttrium stabilized tetragonal polycrystalline zirconia (TPZ), a resin-based composite, an Au-Pt alloy, and a tooth. For all materials, the surface roughness was assessed by profilometry, the surface hydrophobicity was determined by tensiometry, and the zeta potential was measured by electrokinetic phenomena. The arithmetic average roughness was the lowest for the TPZ ceramic (Ra = 0.23 µm ± 0.02 µm), while the highest value was observed for the Au-Pt alloy (Ra = 0.356 µm ± 0.075 µm). The hydrophobicity was the lowest on the TPZ ceramic and the highest on the Co-Cr alloy. All measured streaming potentials were negative. The most important cause of tooth caries is the bacterium Streptococcus mutans, which was chosen for this study. The bacterial adhesion to all material surfaces was determined by scanning electron microscopy. We showed that the lowest bacterial extent was on the amalgam, whereas the greatest extent was on tooth surfaces. In general, measurements showed that surface properties like roughness, hydrophobicity and charge have a significant influence on bacterial adhesion extent. Therefore, dental material development should focus on improving surface characteristics to reduce the risk of secondary caries.